Pelatihan Pembuatan Hand Sanitizer untuk Kader Posyandu Kamboja Kelurahan Tasikmadu Kota Malang - Agung Ari Wibowo; Profiyanti Hermien Suharti; Asalil Mustain; Shabrina Adani Putri (AJAD : Jurnal Pengabdian kepada Masyarakat, 2022)
Posyandu Kamboja was established in 1975 in Tasikmadu Village, Lowokwaru District with an active cadre of 15. The activities of the Posyandu Kamboja include Integrated Healthcare Center for Invant and toddler, Family and Toddler Development Program and Early Childhood Education Post. Healthy life counseling is one of the main activities and is generally a priority in the implementation of Posyandu activities. The development program offered by the community service team to overcome partner problems includes training and assistance in making hand sanitizers as a solution to the limited skills of the Posyandu cadres. The results obtained from the implementation of the training are that posyandu cadres can easily understand the material and skills being taught because the delivery method includes the hands-on practice of making hand sanitizers. In general, there were no obstacles in the activities implementation and the team received very satisfactory feedback from the posyandu cadres.